SINERGI PEMBINAAN KEWIRAUSAHAAN BAGI PEMUDA DI KABUPATEN SLEMAN - Endang Dwi Ratnasari; R. Widodo Triputro (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
Entrepreneurship development for youth is crucial to welcoming the Golden Indonesia Era in 2045, ensuring that this era brings benefits in the form of increased national economic development. Youth are expected to contribute to the nation's economic independence. Capacity building through entrepreneurship development is carried out so that young people are no longer dependent on job providers but are instead able to become entrepreneurs. Entrepreneurship development for youth is certainly the responsibility of all parties, especially local governments through authorized regional apparatus. In 2024, Sleman Regency received the